Numerical Solution of Double Integral of Singular Derivatives Using Trapezoidal Method with Romberg Acceleration - Hanoon, Wafaa Hadi; Naser, Rusul Hassan (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The goal of this paper is to evaluate numerically a double integral of partial Derivatives Using RTRT Method. For Trapezoidal method (one of Newton-Cotes formula) which will be based on two dimensions x and y. In addition to that Romberg acceleration rule will be used to get more accurate results together with less time (faster convergence) and number of subintervals which are involved. We shall refer to this method by RTRT, where R stands for Romberg acceleration and T for Trapezoidal rule.